1996
DOI: 10.1007/bf02055108
|View full text |Cite
|
Sign up to set email alerts
|

Reoperative rates for Crohn's disease following strictureplasty

Abstract: Strictureplasty is a safe and effective procedure for Crohn's disease in selected patients. Reoperative rates are comparable with resective surgery, and most recurrences occur at new sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 14 publications
4
40
0
7
Order By: Relevance
“…One hundred and fifteen dilations (range: [1][2][3][4][5][6][7][8] times/person) were performed in the 40 patients. 4 Long-term avoidance of surgery rate (Fig. 2) Seven patients were operated on because of frequent recurrences or for intractable fistulas, one because of a perforation after the second dilation and one because of massive bleeding unrelated to the dilation procedures (Table IV).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred and fifteen dilations (range: [1][2][3][4][5][6][7][8] times/person) were performed in the 40 patients. 4 Long-term avoidance of surgery rate (Fig. 2) Seven patients were operated on because of frequent recurrences or for intractable fistulas, one because of a perforation after the second dilation and one because of massive bleeding unrelated to the dilation procedures (Table IV).…”
Section: Resultsmentioning
confidence: 99%
“…Patients typically present with symptoms of upper and lower intestinal obstruction. In these patients, usual medical therapy has little effect in curing obstruction [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Controversy exists on the recurrence rate after strictureplasty and resection. 16,[18][19][20][21][22][23] Several invesigators 18,19 have reported no significant differences in rates of recurrence after strictureplasty versus resection. No significant difference is also reported in the recurrence rate after strictureplasty alone and strictureplasty plus resection.…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference is also reported in the recurrence rate after strictureplasty alone and strictureplasty plus resection. 16,20 However, metaanalysis of 7 studies performed by Reese et al 21 showed that patients who underwent resection had significantly longer recurrence-free survival than did those who underwent strictureplasty alone. In the present study, duration between previous operation and recurrence was significantly shorter in patients who underwent strictureplasty than in patients who underwent resection and anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the data in the literature seem to indicate no difference between conservative and conventional surgery in terms of both early perioperative results and long-term recurrence rates [21, 22], few data are currently available concerning SPs and intestinal anastomoses specifically performed on active diseased segments. The aim of this study was to evaluate the perioperative complications, long-term surgical recurrence, and analyze the factors thought to influence them in a consecutive series of prospectively followed patients.…”
Section: Introductionmentioning
confidence: 99%